Affective Stack - A Model for Affective Computing Application Development - Thompson, Nik; McGill, T. (2015)
Affective computing applications hold promise to revolutionize human-computer interaction by enabling more natural and intuitive interaction modalities. These may include the communication of vocal expressions, physiological signals or other non-verbal indicators of underlying affective state. Although the field has experienced substantial expansion in recent years, the tools and techniques utilized are not yet mature or well established. A notable issue is the one-off nature of currently implemented affective computing systems. There is as yet no notion of standardized program architecture and there is no straightforward way to extend the functionality of existing software to include affective components. This paper introduces a new model which describes the affective computing application in terms of a set of loosely coupled functional components. This model encourages a uniform and replicable approach to affective application development in which functional components can be improved independently and subsequently re-used. The model also incorporates existing third party software as a functional component highlighting the potential to build upon existing, well established, software packages. It is hoped that this model and discussion spurs further, focused development in this growing field.